'Uberisation' Is the Future of the Digitalised Labour Market. Issue 2 (December 2015) - Nurvala, Juha-Pekka
The 'Uberisation' of service sectors will become the norm in the future. The driving factor behind this development is a dramatic collapse in transaction costs made possible by new and more developed Internet-based matching platforms. What is emerging can be called the 'People-to-People Economy', a term that describes the diffused nature of the new model. Uberisation, or the new People-to-People Economy, is not the same thing as the 'sharing economy' since the two are based on different economic developments. The centre–right should support this development but at the same time create a social security system for the self-employed entrepreneurs who take part in this new economy.